Understanding inequities in health and health systems in Latin America and the Caribbean: a thematic series - Ana Lorena Ruano; Daniela Rodríguez; Pablo Gaitán Rossi; Daniel Maceira (BMC, 2021)
Abstract Latin America, with its culturally and ethnically diverse populations, its burgeoning economies, high levels of violence, growing political instability, and its striking levels of inequality, is a region that is difficult to define and to understand. The region's health systems are deeply fragmented and segmented, which poses great challenges related to the provision of quality of care and overall equity levels in health and in Latin American society at large. Market, social, and political forces continue to push towards the poorly regulated privatization of public health care in many countries within the region, in detriment of public healthcare services where management capacities are limited. In this first collection of papers, we showcase how the region has tackled, with different levels of success, the incorporation of innovative health system reforms aimed at strengthening governance, participation, and the response to the growing epidemiological and demographic demands of its diverse population. We are delighted that this Special Collection will remain open to house future papers from Latin America and the Caribbean. The region has important experiences and lessons to share with the world. We look forward to learning more about how researchers and practitioners continue to experiment and innovate in their struggle to reach equity in health for all. This thematic series is a platform where the region's lessons and approaches can be shared with the global community of Health Policy and Systems Researchers.